The Influence of Kahoot in Improving Students’ Vocabulary Mastery for The Fifth Grade at SDN 1 Tatura - Nanda Amaliah; Nur Asmawati; Hijrah Syam (Indonesian Journal Publisher, 2025)
This research aims to examine the influence of Kahoot in improving students' vocabulary mastery for the fifth-grade at SDN 1 Tatura. This research employed a quasi-experimental design with a quantitative approach. Data were collected through pre-tests, treatment sessions, and post-tests. The experimental class received treatment using Kahoot. Two classes were selected as samples through purposive sampling: one experimental class and one control class. The data analysis included descriptive statistics, normality tests, homogeneity tests, and hypothesis testing using paired sample t-tests and independent sample t-tests. The findings revealed that the use of Kahoot significantly improved students’ vocabulary mastery. This is evident from the t-test result (12.648), which was higher than the t-table value (2.064) at the 0.05 significance level. This indicates a statistically significant improvement. Based on the data analysis, it can be confirmed that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the use of the Kahoot has a significant influence in improving students' vocabulary mastery for the fifth-grade students.